Atividade elétrica do músculo bucinador antes e após o uso do exercitador facial em crianças respiradoras orais - Krob, Clarissa Flores Oliveira (2008)
This study aimed to analyse the changes occured in the buccinator muscles of mouth breathing children after using Facial Exerciser. Eight children aged between 06 to 11 years old with medical diagnosis of chronic mouth breathing were submitted to surface electromyographic evaluation during rest, sucking and blowing; previously to the beginning of therapy (T0) and approximately at 10 (T1) and 40 (T2) days of treatment. The results were quantified in RMS (root mean square) and shown in eV (microvolt). The normalized data were compared and statistically analysed through double ANOVA and ANOVA of Friedman, as well as the Tuckey Test. The results concerning buccinator muscle activity showed a tendency to decrease in the end of 40 days using the Facial Exerciser. There was an increase in the electrical activity average of both muscles, however statistically significant results were not found. The results were more expressive after the 10 days of treatment than after 40 days using the device, despite of not showing significant statistical difference. Based on these findings, it can be considered that the use of Facial Exerciser in mouth breathing children has cooperated with decreasing of buccinators muscles activity during rest position. During blowing there was an increase in the average of the activity in both muscles.